Analisis Informasi Penerbitan dan Topik Populer Terbitan Berkala Ilmu Perpustakaan dan Informasi di Indonesia - Nashihuddin, Wahid; Hidayatullah, Fauzan; Putra, Kadek Aryana Dwi (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2020)
Library and information science periodicals in Indonesia have a variety of publishing policies and topics of discussion, as the information showed on the publication’s website. This study aims to determine: (1) the identity of the library and information science periodicals in Indonesia which can be accessed online; (2) the publishing information on those periodicals website; and (3) the popular topics of those periodicals. The research data used qualitative data, which was sourced from information searching in the SINTA Database of the Ministry of Research, Technology and Higher Education, ISSN LIPI, and the website of library and information science periodicals in Indonesia The determination of the popular topics of this publication using the online application Voyant Tools. The results showed: (1) there are 61 periodicals of library and information science in Indonesia that can be accessed online, most of which are publications from universities and have not been nationally accredited (only about 27 periodicals have been accredited); (2) most publications have informed their publishing policies through websites, but the information needs to be corrected and updated regularly; (3) the most popular topic was the "library". Apart from discussing these popular topic, the periodicals also discuss other topics, such as information science, management, archiving, data, literacy, digital services, publications, librarians, collections, documentation, information and communication technology, etc.